Elemental Composition and Sources of Fine Particulate Matter (PM2.5) in Delhi, India - Sharma, S. K.; Mandal, T. K. (Bulletin of environmental contamination and toxicology, 2023)
In this study we have analysed the elemental composition of fine particulate matter (PM 2.5 ) to examine the seasonal changes and sources of the elements in Delhi, India from January, 2017 to December, 2021. During the entire sampling period, 19 elements (Al, Fe, Ti, Cu, Zn, Cr, Ni, As, Mo, Cl, P, S, K, Pb, Na, Mg, Ca, Mn, and Br) of PM 2.5 were identified by Wavelength Dispersive X-ray Fluorescence Spectrometer. The higher annual mean concentrations of S (2.29 µg m -3 ), Cl (2.26 µg m -3 ), K (2.05 µg m -3 ), Ca (0.96 µg m -3 ) and Fe (0.93 µg m -3 ) were recorded during post-monsoon season followed by Zn > Pb > Al > Na > Cu > Ti > As > Cr > Mo > Br > Mg > Ni > Mn > and P. The annual mean concentrations of elemental composition of PM 2.5 accounted for 10% of PM 2.5 (pooled estimate of 5 year). Principal Component Analysis (PCA) identified the five main sources [crustal/soil/road dust, combustion (BB + FFC), vehicular emissions (VE), industrial emissions (IE) and mixed source (Ti, Cr and Mo rich-source)] of PM 2.5 in Delhi, India.